The Relationship Between Intellectual Humility and Spiritual Struggle among Undergraduate Students - Tobechi Uzoigwe; Chinonso Uzoigwe (MultiTech Publisher, 2023)
Purpose . This study assesses relationship between spiritual struggle and intellectual humility among undergraduate students. Research Methodology A cross-sectional research design using random sampling technique was adopted to recruit 158 students from undergraduate students of Nassarawa state university Keffi. Instruments administered included Religious and Spiritual Struggles Scale (RSSS) and the general intellectual humility scale. The T-test and correlations were used for statistical analysis. Results showed a significant, weak , and direct relationship between Moral struggle and intellectual humility [r(158)=.0.264, P< .05]. Ultimate meaning has a significant relationship with intellectual humility [t(158) = 2.89; p< 05].. Muslims recorded lower level of divine, interpersonal, demonic and moral struggle than christians. Limitations The study is crossectional correlation design and is difficult to draw causation.. Various components of Intellectual humility were not examined. The study is limited to college students at a tertiary university and hence findings might not be generalised. Contribution ; The findings of this study provide information on students levels of spiritual struggles as a foundation for developing intervention for improving their spiritual wellbeing. Practical Implication; It was concluded that intellectual humility , despite its benefits, can be related to lack of conviction about the meaning of life and lead to hesitation in taking ethical decision. . It is recommended that students should seek professional help regarding their spiritual struggles . Novelty ; This is a the first study that examines intellectual humility and spiritual struggles in Nigeria and thus unravels dark side of intellectual humility in ones spiritual life.